ANALISIS PENGENDALIAN INTERN ATAS PENJUALAN AIR, DAN PIUTANG DAGANG PADA PDAM TIRTA KHATULISTIWA KOTA PONTIANAK - B1031131101, Nindy Puspitasari (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Municipal Water Company Thirta Khatulistiwa Pontianak is the only Drinking Water Company in Pontianak City owned by the government of Pontianak City, where within the Municipal Water Company of Pontianak City. Sales is one of the efforts to achieve company goals, which become an indication of the problem in this research is Internal control system should be set in all aspects, both in terms of management and systems and procedures because the internal control system serves as a grip in achieving company goals, as a tool to maintain Company property, check employees' accuracy, improve efficiency and encourage compliance with management policies. The results showed that the internal control of sales systems and accounts receivable system is good enough. This is because the company has applied the principles of adequate internal control such as the strict separation of duties and the use of appropriate forms of company rules.Keywords : Internal Control of Water Sales and Accounts Receivable.